Churg-Strauss syndrome: A case report - Dinić, Miroslav Ž.; Kandolf Sekulović, Lidija; Zolotarevski, Lidija; Zečević, Radoš D. (Vojnosanitetski pregled, 2017)
Introduction. Churg-Strauss syndrome (CSS) is an allergic granulomatous angiitis, a rare disease of small and medium arteries and veins, associated with the presence of perinuclear antineutrophil cytoplasmic antibodies (p-ANCA). According to the American College of Rheumatology (ACR), there are four or more criteria out of six for the diagnosis: asthma, eosinophilia (> 10% in peripheral blood), paranasal sinusitis, pulmonary infiltrates, histological evidence of vasculitis with extravascular eosinophils, and mononeuritis multiplex or polyneuropathy. Case report. We reported a female patient, aged 80 years, with asthma for many decades and repeatedly verified eosinophilia in peripheral blood, in which CSS was suspected only after the occurrence of skin changes in the form of vesicles, vesiculopustule, purpuric macula, papule and petechiae. Further tests verified pulmonary infiltrates, paranasal sinusitis, extravascular eosinophils on histopathologic sample of skin tissue, and polyneuropathy. The treatment started with methylprednisolone (60 mg/d, with decreasing doses), and continued with pulse doses of cyclophosphamide (800 mg once monthly), also corticosteroid ointment for skin lesions. Conclusion. Despite long-standing pulmonary symptoms and laboratory findings of eosinophilia, the appearance of skin changes raised suspicion of possible CSS. Skin changes resolved and the patient was reffered to rheumatologist.   Key words: churg-strauss syndrome; diagnosis; skin diseases; histological techniques.